Invasion of Parthenocissus quinquefolia (L.) Planch in the forest-steppe of Ukraine - Blinkova, Olena; Makarenko, Natalia; Raichuk, Liudmila; Havrylnuk, Yulia; Grabovska, Tetiana; Roubik, Hynek (Ecological Questions, 2022)
Research needs of adaptation mechanisms of invasive alien species arises in connection with the naturalization of species of the genus Parthenocissus Planch in forest ecosystems of Ukraine. The results showed that P. quinquefolia has a wide range of values of edaphic and climatic factors. The populations of P. quinquefolia differ according to the degree of anthropogenic transformation of the ecotope, the ecological conditions formed, and the allocation of coenotics. The biomorphological characteristics of the species variability are shown on the gradient of anthropogenic transformation. Diagnostic parameters of P. quinquefolia under the conditions of anthropogenic transformation are the number of crotches of the tendrils and the length of the tendrils. The number of flowers per plant is characterized by the highest level of variation and belongs to the V class of variability. The smallest plasticity is characterized by the diameter of the stem. Vitality analysis indicated that cenopopulations of P. quinquefolia belong to the equilibria or prosperous population types, regardless of the intensity of the anthropogenic factor.